2022
DOI: 10.3390/microorganisms10020440
|View full text |Cite
|
Sign up to set email alerts
|

A Legume Host Benefits More from Arbuscular Mycorrhizal Fungi Than a Grass Host in the Presence of a Root Hemiparasitic Plant

Abstract: In nature, most plants parasitized by root hemiparasites are also colonized by mutualistic arbuscular mycorrhizal (AM) fungi, highlighting the prevalence of this tripartite interaction. AM colonization is generally found to improve the growth of parasitized legumes but has little impact on grass hosts parasitized by root hemiparasites, and the underlying mechanisms are still unclear. In this study, we conducted a pot experiment to test the influence of AM fungus (Glomus mosseae) on the growth and photosynthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…They are formed by bryophytes, pteridophytes, gymnosperms and angiosperms and are ubiquitous in most temperate and tropical ecosystems including agricultural systems. According to Sui et al 18 , legumes have a good mycotrophic status and arbuscular mycorrhizas are found in their roots. The fungal partners in AM associations are remarkably abundant, accounting for 5-50% of the microbial biomass in agricultural soils, with the fungal phylum, Glomeromycota being the most common 19 .…”
Section: Discussionmentioning
confidence: 99%
“…They are formed by bryophytes, pteridophytes, gymnosperms and angiosperms and are ubiquitous in most temperate and tropical ecosystems including agricultural systems. According to Sui et al 18 , legumes have a good mycotrophic status and arbuscular mycorrhizas are found in their roots. The fungal partners in AM associations are remarkably abundant, accounting for 5-50% of the microbial biomass in agricultural soils, with the fungal phylum, Glomeromycota being the most common 19 .…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to mycorrhizal colonization rates of L. chinensis , P. distans , and A. adurgens in the present study, which are 25.00%, 16.89%, and 46.95%, respectively. Among them, the mycorrhizal colonization rate of A. adurgens was higher than that of the other two grasses, which may be due to the fact that the mycorrhizal colonization rate of AMF and legume plants is generally higher than that of gramineous plants (Sui et al, 2022). In this study, AMF significantly improved the biomass of A. adsurgens , indicating that the symbiosis of AMF and A. adsurgens effectively alleviated the phytotoxicity caused by Cd and salt during plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…Fungus-based biofertilizers, in particular, have been shown to improve plant growth and health by providing essential nutrients and improving soil health. Particularly, the advantageous effects of arbuscular mycorrhizal fungi (AMF) on a variety of crops, such as cereals, legumes, and vegetables, have been extensively studied (Chen et al, 2018; Begum et al, 2019; Khan et al, 2022; Sui et al, 2022).…”
Section: Introductionmentioning
confidence: 99%